Characterization of Microbial Degradation Products of Steviol Glycosides - Gert Steurs; Nico Moons; Luc Van Meervelt; Boudewijn Meesschaert; Wim Michel De Borggraeve (Molecules, 2021)
Steviol glycosides were subjected to bacteria present in a soil sample collected from a Stevia plantation in Paraguay. During the incubation experiments, next to the aglycon steviol, steviol degradation products were also formed. X-ray analysis and NMR methods in combination with chemical synthesis and GIAO NMR calculations were used to fully characterize the structure of these compounds as a tricyclic ketone and the corresponding reduced form. They were nicknamed monicanone and monicanol. The latter has the (S)-configuration at the alcohol site.